Covid-19 during Pregnancy – Histopathological Lesions of the Placenta - Kummer, Julia; Ameli, Giada; Jebens, Anja; Königbauer, Josefine; Mihajlov, Valentin; Nacke, Anna Kaarina; Pham, My Hanh; Rickert, Christian; Simon, Luisa; Schellenberg, Tim; Hellmeyer, Lars (Zeitschrift für Geburtshilfe und Neonatologie, 2023)
Introduction Pregnant women and their offspring represented a vulnerable patient collective during the Covid-19 pandemic. Beyond the direct effect of SARS-CoV-2 via vertical transmission, an indirect impact on the fetus can occur through placental lesions deteriorating placental villous function. We performed a histopathological analysis of placentas of parturients with SARS-CoV-2 compared to healthy controls.Methods and materials Between February 2022 and July 2022 we conducted a prospective case–control study analyzing placental specimens of parturients with SARS-CoV-2 infection compared to specimens of placentas of healthy controls. Patient history, Covid-19-specific symptoms, and obstetric outcomes were recorded. Statistical analysis was performed.Results During the observation period 71 patients were included with a gestational age 37 1/7–41 5/7 weeks. Thirty-six patients presented with SARS-CoV-2 infection. The control group consisted of 35 patients and showed no placental abnormalities. Among SARS-CoV-2-positive parturients, 66.7% of placentas of the case group showed histopathological abnormalities classified as vascular or inflammatory abnormalities. 22.2% of placentas showed acute ischemic infarction areas. 8.3% of placentas showed subchorionic layered thrombi. There was one case of severe acute subchorionitis. SARS-CoV-2 increased the risk of placental lesions significantly (OR 3.000, CI 1.890–4.762, p=0.0001). Placental lesions had no significant impact on perinatal acidosis (OR 0.455, CI 0.044–4.667, p=0.498) or number of cesarean sections (OR 2.314, CI 0.717–7.473, p=0.156).Conclusion SARS-CoV-2 infection during labor and delivery increased the risk of adverse outcomes. Histopathological analysis indicated that the placenta as a maternal-fetal interface was affected by SARS-CoV-2, leading to systemic vasculopathy and inflammation.
Keywords: SARS-CoV-2; Covid-19 pandemic; Covid-infection during pregnancy; histopathological changes of the placenta